MANAGEMENT OF CASH FLOWS OF THE ENTERPRISE AND THEIR OPTIMIZATION - Natalie V. Gryzunova; Mikhail N. Dudin; Oleg V. Talberg (Статистика и экономика, 2016)
The purpose of this work is the analysis of structure and process of management of cash ﬂows of the enterprise, researchof a ﬁnancial position and development of recommendationsabout increase of effective management of cash ﬂ ows. When performing work various methods of research were applied:ﬁ nancial, coefﬁ cient, ekonomiсo-mathematical, etc. As a result of the analysis reserves of increase of management efﬁciency are revealed and models of free cash ﬂows, the most actual for group of the considered enterprises are offered.